El Mercado Integrado Latino Americano (MILA). Contexto, Hipótesis y Reflexiones - Palomino Selem, Carlos (2010)
The integration and merger of the stock exchanges have the propose to increase their participation in the international or regional capital markets; but this will be possible if the stock exchange’s transaction costs are competitive respect to others markets. The MILA is an interesting experience because the integration imply three countries that have similar economic performance, but it will be necessary that the economic model continue without modification in the member countries.